Ritos fúnebres na Eneida - Rêgo, Nathália Pinto do (2015)
This paper proposes a study of the Aeneid, by Virgil, specifically the episode of Miseno's funeral, described in Book VI of the poem, and Pallas's funeral, present in Book XI. From the description of the funeral ceremonies performed by the poet, we will do a study on the cultural and religious aspects involved in this kind of religious practice, highlighting its importance within the archaic societies. Funeral rites composes some of the oldest customs of these people, and observed their achievement from primitive societies, given that the archaic antiquity already admitted a belief in the permanence of the soul after death, considering life on earth as a passage. The funeral rites arise as a way to end the earthly existence in the grave, beginning a life that is beyond the material plane. If the funerals were not accomplished, the soul would remain wandering in the earthly world, in the form of ghost or larva, tormenting the living, as a way of claiming their burial in order to finally reach the gateway to the underworld.